Preparation of sustainable asphalt pavements using polyethylene terephthalate waste as a modifier - Mulla Jaffar Emad A. Al; Sahar M. Makky (Zaštita Materijala)
Industrial development and contemporary life style led to spread a large amounts of non-biodegradable plastic waste. This paper aims to study the effects of recycling polyethylene terephthalate (PET) plastic waste which is a type of disposable plastic packaging waste as an asphalt modifier, to create a sustainable asphalt pavement and improving the rheological properties and temperature susceptibility. PET waste was blended with asphalt cement in three percentages (0.5%, 0.75%, and 1.0%) by mass of asphalt cement. The performance of modified asphalt samples have been studied and compared with an unmodified asphalt binder. The penetration, softening point and ductility were carried out to evaluate the influence of adding waste PET to asphalt on binder characteristics, binder stiffness at different temperatures also studied and all markedly improved. The results show that adding PETW has a significant effect on the rheological behavior and binder stiffness in high temperatures. This study indicate that waste PET has enhance asphalt properties to minimize the paving costs and reduce solid waste environmental problems.